QSAR model and microscopic mechanism analysis of dye removal by coagulation of aluminum chloride under alkaline conditions - Zhang, Meilan; Qin, Shengnan; Tan, Yujia; Shen, Zhemin (Frontiers in Environmental Science, 2023)
Inorganic AlCl3 coagulation is a typical representative of traditional coagulants for removing industrial dye wastewater. In this study, the color removal rate of traditional inorganic AlCl3 coagulation system for dyes was alkaline > neutral > acidic. Under alkaline condition, the colloid formed by the hydrolysis of AlCl3 was positively charged, which was easily combined with negatively charged anionic dyes to achieve the removal effect by electrostatic adsorption. Therefore, this work focused the relationship between the dyes removal behavior and molecular parameters under alkaline condition based on the experimental removal rate and correlation analysis. The quantitative structure activity relationship (QSAR) models were built up by color removal rates (Rexp) of 41 dyes and 46 molecular parameters of each dye computed by the density functional theory (DFT) method. The recommended model under alkaline condition (i.e., pH=10) was Rpre = -0.503 + 0.001 SAA + 0.700 q(C-)x - 0.003 ESPMAX - 3.932E - 5 EB3LYP. Internal validation, external validation, statistical test, Y-randomization and applicability domain test indicated the optimal model was stability, accurate, reliability and predictive. The result of correlation analysis and optimal QSAR model showed that the two key molecular parameters that affected the color removal of dyes by AlCl3 under alkaline condition was surface area (approx) (SAA) and molecular weight (MW). Moreover, the coagulation mechanism of AlCl3 for dye removal under alkaline condition was electrostatic adsorption and hydrogen-bonding adsorption, and hydrogen-bonding adsorption was the main force.